YKL-40 promotes chemokine expression following drug-induced liver injury via TF-PAR1 pathway in mice - Jing-Lun, Zhan; Shuang, Chai; Li-Mei, Zhao; Xiao-Dong, Liu (Frontiers in Pharmacology, 2023)
The inflammatory factor YKL-40 is associated with various inflammatory diseases and is key to 2 remodeling inflammatory cells and tissues. YKL-40 (Chi3l1) promotes the activation of tissue factor (TF), leading to intrahepatic vascular coagulation (IAOC) and liver injury.TF is a key promoter of the exogenous coagulation cascade and is also involved in several signaling involving cell proliferation, apoptosis, charring, migration and inflammatory diseases pathways. However, the effect of YKL-40-induced TF-PAR1 pathway on the expression of downstream chemokines remains unknown. In this study, we established a liver injury model using Concanavalin A (ConA) in C57 BL/6 mice. We found that overexpression of YKL-40 increased the expression of TF, protease-activated receptor 1 (PAR1), CCL2 and IP-10 in mice and exacerbated the severity of liver injury. However, blocking the expression of TF significantly reversed the extent of liver injury. Overall, our current study reveals a pro-inflammatory role of the TF-PAR1 pathway induced by YKL-40. yKL-40 promotes the expression of CCL2 and IP-10 by inducing the TF-PAR1 pathway in the liver, increases the recruitment of inflammatory cells, and ultimately leads to liver injury. These findings provide a new avenue for clinical treatment of drug-induced liver injury.